Overall survival in patients with metastatic renal cell carcinoma in Russia, Kazakhstan, and Belarus: a report from the RENSUR3 registry. Issue 3 (25th December 2020) - Tsimafeyeu, Ilya; Shatkovskaya, Oxana; Krasny, Sergei; Nurgaliev, Nurzhan; Varlamov, Ilya; Petkau, Vladislav; Safina, Sufia; Zukov, Ruslan; Mazhbich, Mikhail; Statsenko, Galina; Varlamov, Sergey; Novikova, Olga; et al.
Abstract: Background: Real‐world data describing outcomes of treatment among metastatic renal cell carcinoma (mRCC) patients are limited and heterogeneous. Aim: RENSUR3 registry study assessed real‐world data on the use of therapies in mRCC and overall survival (OS) in Russia, Kazakhstan, and Belarus. Methods: Patients were included in the retrospective multicenter registry study. To be eligible, patients were required to have mRCC diagnosed from January 2015 to January 2016. Anonymized data were collected through an online registry. The outcomes of interest were patient characteristics, treatment patterns, and OS. Results: 1094 mRCC patients were identified. Mean age was 62.3 (SD, 11.2) years. Four hundred and forty‐four (41%) patients were 65 years and older. Primary tumor has not been removed in 503 (46%) patients. Subtype of RCC based on WHO classification (clear‐cell or other) has been reported in 402 (37%) patients. In total, 595 (54.4%) patients received systemic therapy for metastatic disease. 58% of elderly patients (≥65) were not treated compared to 37% of younger patients. Cytokines and targeted therapy were used in 298 (50.1%) and 297 (49.9%) of 595 treated patients, respectively. Median OS was 11.9 months (95% CI 10.9‐12.9). The 1‐ and 3‐year OS rates were 49.6% and 19.3%. Conclusions: Half of patients received no systemic therapy or had only cytokines for mRCC in Russia, Kazakhstan, and Belarus, which doubtless negatively affected OS in this population. Novel therapies should be considered as life prolonging and a priority.